Development of monitoring system with IoT technology for harvested energy from burning process / Amardeep Singh Dhillon ... [et al.] - Dhillon, Amardeep Singh; Mohd Said, Rahaini; Krishnan, Nagen (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
In this paper, it is being proposed on the development of the product that consists of thermoelectric generator (TEG) with integrating IoT system. The product is mainly concerned to harvest the heat energy using biomass sources to generate electricity, DC and AC electricity for community need. Besides that, analytical graphs have been produced based on the data collected and these data can be viewed into a different dimension such as gadget based or web view based as the data will be called-off from each time the burning process happens.